RELASI KUASA DALAM TAFSIR ANALISIS TAFSIR TEMATIK MODERASI BERAGAMA KEMENTERIAN AGAMA (PENDEKATAN SYSTEMATIC LITERATURE REVIEW) - Akhmad Nizaruddin (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2025)
The paradigm shift in the composition of Qur’anic exegesis from individual works to collective or institutional efforts, along with the involvement of the Ministry of Religious Affairs in publishing exegetical works, indicates the presence of power relations in the production of tafsir. Qur’anic interpretation cannot be separated from the worldview of the exegete, which means the style and ideology of a tafsir are heavily influenced by the interpreter and their understanding of the surrounding socio-political realities. The theme of religious moderation in the Thematic Qur'anic Exegesis represents the manifestation of implementing the government’s programs and mission by the Ministry of Religious Affairs as an institution responsible for religious development. This study employs the Systematic Literature Review (SLR) method, with the research objects being articles indexed in Google Scholar, selecting literature from scientific publications in journals using the keywords